2012
DOI: 10.1111/j.1551-2916.2012.05292.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Cycling of Suspension Plasma Sprayed Alumina‐YSZ Coatings Containing Amorphous Phases

Abstract: Thermal cyclic test at 1080°C for various numbers of cycles was performed on suspension plasma‐sprayed coatings of alumina‐yttria‐stabilized zirconia composites and yttria‐stabilized zirconia ( YSZ ). The structural variations of composite coatings were studied to verify the possibility of production of nano‐composite coatings with nano‐dispersed oxides. The results showed that this composite exhibited a lower thermally grown oxide growth than that of the YSZ . New multi‐constituent composites formed of alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…As corundum ( H = 15 GPa) 38 is harder than 8YSZ ( H = 13.3 ± 0.3 GPa in this study), it was expected that the composites hardness would be increased by the addition of corundum. The addition of alumina into zirconia increases the densification by changing the diffusion mechanism from grain boundary to volume diffusion and significantly decreases the activation energy, also the high‐temperature sintering causes internal sintering of the materials resulting in high hardness 40–42 . The corundum smaller particles size (0.2–0.4 μm, see Figure 4) more effectively refines the grain size and the grain boundaries of 8YSZ, thus hardness increases with decreasing particle size, this is known as the Hall–Petch effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As corundum ( H = 15 GPa) 38 is harder than 8YSZ ( H = 13.3 ± 0.3 GPa in this study), it was expected that the composites hardness would be increased by the addition of corundum. The addition of alumina into zirconia increases the densification by changing the diffusion mechanism from grain boundary to volume diffusion and significantly decreases the activation energy, also the high‐temperature sintering causes internal sintering of the materials resulting in high hardness 40–42 . The corundum smaller particles size (0.2–0.4 μm, see Figure 4) more effectively refines the grain size and the grain boundaries of 8YSZ, thus hardness increases with decreasing particle size, this is known as the Hall–Petch effect.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of alumina into zirconia increases the densification by changing the diffusion mechanism from grain boundary to volume diffusion and significantly decreases the activation energy, also the high-temperature sintering causes internal sintering of the materials resulting in high hardness. [40][41][42] The corundum smaller particles size (0.2-0.4 μm, see Figure 4) more effectively refines the grain size and the grain boundaries of 8YSZ, thus hardness increases with decreasing particle size, this is known as the Hall-Petch effect. However, as the corundum particles size increases, its number density gradually decreases which allows a small increase in 8YSZ grain size that contributes to hardness value degradation of the composites.…”
Section: Mechanical Properties and Thermal Expansion Coefficientmentioning
confidence: 99%
“…Currently, LaMgAl 11 O 19 (LMA) is the most widely studied rare-earth hexaaluminate. It was found that a YSZ/LMA double-ceramic structure had a longer service life than a single-layer YSZ or LMA during thermal cycling tests [24][25][26][27][28]. Additionally, the YSZ/LMA double-ceramic structure exhibited better corrosion resistance to molten salts such as V 2 O 5 , Na 2 SO 4 + V 2 O 5 , and CAMS [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Yttria (Y 2 O 3 ) stabilized zirconia (ZrO 2 , YSZ) is one of the most extensively studied oxide ceramic material, having numerous applications in the fields of bio-ceramics, fuel cells, sensors, nanomaterials, thermal/diffusion barrier coatings, and nuclear waste management [1][2][3][4][5][6][7][8][9][10][11][12]. In nuclear industry, cubic zirconia is considered as a potential inert host matrix for incineration of excess plutonium (Pu) [13][14][15][16][17][18] and transmutation of transuranic nuclear wastes [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%